Overview of the Cardiac Conduction System: A Narrative Literature Review - Hidayat, Rachmat (Sriwijaya Journal of Internal Medicine, 2023)
The conduction system of the cardiac initiates and coordinates the electrical signals that cause rhythmic and synchronous contraction of the atria and ventricles. This literature review aims to describe the electrophysiology of the cardiac conducti on system. Electrical impulses usually arise in the sinoatrial (SA) node. The SA node is innervated by sympathetic and parasympathetic nerves. Each act ion potential moves rapidly from cell to cell and through the myocardium of the atria, onto the atrioventricular node (AV node), and causes both atria to contract and begin systole. The AV node, located on the right atrial wall superior to the tricuspid valve and anterior to the coronary sinus ostium, conducts action potentials into the ventricles. From the AV node, the conducting fibers converge t o form the bundle of His (atrioventricular bundle) within the posterior border of the interventricular septum.